TEACHING READING COMPREHENSION OF RECOUNT TEXTS THROUGH HERRINGBONE TECHNIQUE - Wahyuni, Sri; Sudarsono, Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research investigated the evidence that the Herringbone technique was useful to help students to comprehend reading texts. This was a pre-experimental research with one group pre-test and post-test design. There were 37 students that participated in this research. The data were collected by objective tests and analyzed by paired t-test and effect size formula using Cohen’s index. Based on the research findings, the null hypothesis (H0) was rejected, while alternative hypothesis (Ha) was accepted. The t-obtain (4.03) was bigger than t-table (2.021) by the degree of freedom 36. The effect size was categorized moderate since the r-value was 0.30, within 0.2 up to 0.8. To sum up, the significance of using Herringbone Technique to help students to comprehend a recount text of Year-8 students of SMP Negeri 14 Pontianak in Academic Year 2017/2018 was moderate.Keywords: Herringbone Technique, Personal Recount Text, Literal and Inferential Questions